Comparative Anatomy and Histology of Black Pomfret (Formio niger) and Nile tilapia (Oreochromis niloticus) Kidney - Nurul Safitri Apriliani; Muhammad Jafar Luthfi (Biology, Medicine, & Natural Product Chemistry, 2017)
Black pomfret and nile tilapia are belonging to order Perciformes. Both fish are live in different habitat. Black pomfret is marine water whereas nile tilapia is in freshwater. The purpose of the study was to determine anatomy and histology of the kidneys structures in both fishes. Histological preparations were done using paraffin method, with Hematoxylin-Eosin (HE) staining. The results, showed that Black pomfret and nile tilapia have y-shape kidney. Nile tilapia has darker red colour and softer texture than black pomfret kidney. Histologically, black pomfret and nile tilapia kidneys have a distal tubule, proximal tubule, glomerulus and lymphoid tissue. Glomerular diameter of nile tilapia (69,22 µm) was larger than pomfret (61,25 µm). It can be concluded that differences between anatomical and histological structure of kidney are affected by habitat differences.